2021
DOI: 10.1016/j.lithos.2020.105851
|View full text |Cite
|
Sign up to set email alerts
|

Tracking metal evolution in arc magmas: Insights from the active volcano of La Fossa, Italy

Abstract: The mineralization potential of arc magmas depends, among other factors, on the timing of sulfide melt saturation relative to magma differentiation and to exsolution of a magmatic fluid phase. In fossil mineralized or barren systems, understanding the evolution of metals along the magma differentiation path is often hindered by late magmatic processes and hydrothermal alteration. To better understand the process of metal evolution "caught in the act" in crustal reservoirs, we analyzed magmatic sulfides and mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Immiscible sulfide melts have been considered to be the major sulfide phase in arc felsic magmas as they are in mafic magmas 117,123,124,126,174,175 . However, monosulfide solid solution can be the predominant sulfide phase in some felsic intrusive rocks 47,172,176,177 .…”
Section: [H1] Summary and Future Directionsmentioning
confidence: 99%
“…Immiscible sulfide melts have been considered to be the major sulfide phase in arc felsic magmas as they are in mafic magmas 117,123,124,126,174,175 . However, monosulfide solid solution can be the predominant sulfide phase in some felsic intrusive rocks 47,172,176,177 .…”
Section: [H1] Summary and Future Directionsmentioning
confidence: 99%
“…However, it is important to keep in mind that Nisyros is an open/active magmatic‐hydrothermal system with a shallow water saturated reservoir and thus it is likely that even if the system had enough metals to form a mineralization most chalcophile and siderophile elements would have already partitioned into the exsolving volatile phase, rendering the residual magma barren. Even so, magmatic processes controlling metal evolution in such active magmatic arc systems are similar to those characterizing magmas associated to porphyry Cu systems and can thus provide essential information on the early stages of ore genesis (Costa et al., 2021). Further detailed studies of magmatic sulfides, in similarly well constrained and magmatic‐hydrothermal systems can help investigate the potential of using such petrographic and geochemical evidence as tools for distinguishing barren from fertile or potentially fertile geological areas.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that magmatic sulfide phases are present in a variety of rocks corresponding to diverse geodynamic settings, lithologies, and magma compositions (Z. Chen et al., 2021; Costa et al., 2021; Georgatou & Chiaradia, 2020; Mandon et al., 2021; Rottier et al., 2020). It thus appears that many magmatic systems have the potential to reach sulfide saturation at some point during their lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Most siderophile and chalcophile elements eagerly partition into an aqueous fluid phase, especially in the presence of sulfur and halogens [27][28][29][30][31][32][33][34][35][36][37][38]. The transport and mobilization of ore elements can also be assisted by the formation of metal-rich sulfide magma [39][40][41][42][43][44][45]; pulsated build-up of large, fluidsaturated sub-volcanic magma chambers [46][47][48][49][50][51][52]; or by flotation of metal-rich sulfides and other ore minerals (e.g., magnetite) on gaseous bubbles in lava flows and shallow melt conduits [53][54][55][56][57][58][59]. Recent discoveries of native metals (Cu, Ag, Au) and Cu-Sn-Co-Ag alloys in vesicular basalts from Hawaii, Vesuvius, Etna and Stromboli suggest metal pre-concentration and enrichment via vapor-assisted fractional crystallization during lava solidification prior to later-stage hydrothermal alteration and the remobilization of ore metal components [60,61].…”
Section: Introductionmentioning
confidence: 99%